1989
DOI: 10.3109/02688698909002790
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Intervertebral Disc Protrusion: Experience of 67 cases and review of the literature

Abstract: Sixty-seven cases of thoracic intervertebral disc protrusion are reported with an analysis of clinical and radiological findings. The findings include the fact that male: female ratio is approximately equal, peak incidence is in the 3rd to 5th decade with another peak at age 30-40 in men. This latter peak appears to be associated with trauma which is otherwise uncommon. Results of surgical treatment indicate that the transthoracic and costotransversectomy routes are almost equally effective; laminectomy is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
2
6

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 40 publications
2
28
2
6
Order By: Relevance
“…Distribution according to gender showed a marked female predominance in the present series consistent with the literature [4,6,7,9,14,17,19,28,30], perhaps due to changes in the hormonal status during menopause and its consequences on calcium-phosphorus metabolism. In the present series, all of the lesions were observed in the lower half of the thoracic spine with a peak of frequency between the eighth and twelfth thoracic vertebrae.…”
Section: Discussionsupporting
confidence: 91%
“…Distribution according to gender showed a marked female predominance in the present series consistent with the literature [4,6,7,9,14,17,19,28,30], perhaps due to changes in the hormonal status during menopause and its consequences on calcium-phosphorus metabolism. In the present series, all of the lesions were observed in the lower half of the thoracic spine with a peak of frequency between the eighth and twelfth thoracic vertebrae.…”
Section: Discussionsupporting
confidence: 91%
“…[1][2][3] Wood et al 4 reported 37% of the subjects in their study to have asymptomatic thoracic disc prolapse evident on MRI.…”
Section: A B Bmentioning
confidence: 99%
“…1,[5][6][7][8][9] Abnormal neurological symptoms are the second most common presentation. [1][2][3] These include, sensory (paraesthesia, dysaesthesia and numbness), motor and bladder or bowel disturbance. [1][2][3] There are few case reports describing abdominal pain, resulting from a thoracic disc prolapse.…”
Section: A B Bmentioning
confidence: 99%
See 2 more Smart Citations